Pengaruh Metode SAS terhadap Hasil Belajar Membaca Bahasa Indonesia Kelas 1 SDIT Islamia - Wafa Lu'luah Mardhotillah; Ummul Qura (Ideas Publishing, 2023)
The method used in reading class must be able to provide maximum knowledge to students. This study aims to determine the effect of the SAS (Structural Analysis Synthetic) method application on reading outcomes in Indonesian Subject in grade 1st SDIT Islamia. This research using a quantitative experiment design with a sample of 24 students in experimental class and 24 students in control class and data analysis through the classical assumption test and t-test. Results of the study showed that the mean post-test score of the experimental class was higher than that of the control class. In addition, it is known that the value of tcount > ttable, so it can be concluded that the SAS method application in reading class in 1st grade of SDIT Islamia has a significant influence on student learning outcomes.